Emotion Words Modulate Early Conflict Processing in a Flanker Task: Differentiating Emotion-Label Words and Emotion-Laden Words in Second Language. (December 2019) - Zhang, Juan; Teo, Timothy; Wu, Chenggang
Emotion words modulate conflict processing, even at an early stage (i.e., N200). However, the previous studies implicitly mixed emotion-label words and emotion-laden words together and mostly concentrated on first language (L1) rather than on second language (L2). The current study aimed to investigate whether L2 negative emotion-label words, negative emotion-laden words, and neutral words would affect conflict processing in a flanker task by using event-related potential (ERP) measurements. Twenty Chinese-English bilinguals completed a modified flanker task to decide the color of the target words. The results revealed that only L2 negative emotion-label words elicited larger left frontal N200 in the incongruent condition than in the congruent condition. No significant difference between the two conditions was observed for L2 negative emotion-laden words or neutral words. This research demonstrated that L2 emotion words could also modulate early conflict processing, at least for L2 negative emotion-label words.